Internal Quality Assurance System (SPMI) As An Ecosystem To Form A Sustainable Quality Culture at SDI Mohammad Hatta Malang - Zahra, Syifa Amalia; Anggraeni, Tarisa Nurul (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3623, 2025)
The quality of education in Indonesia is still relatively low compared to other countries, which causes various problems in improving the quality of national education. As an effort to overcome this, the government has developed an Internal Quality Assurance System (SPMI) which is implemented at the level of educational institutions as the main mechanism for quality assurance. The SPMI ecosystem approach aims to form a sustainable quality culture through an independent and continuous cycle in educational units, thereby encouraging consistent quality improvement. This study aims to examine the process of implementing SPMI at SDI Muhammad Hatta, Malang City, with a descriptive qualitative method using primary and secondary data analyzed through triangulation techniques. The results of the study show that the implementation of SPMI follows the stages of the PDCA cycle (Plan, Do, Check, Act) with the support of supporting actors such as school principals, involvement of school residents, and parental support, although there are obstacles in infrastructure facilities, especially the lack of teachers' understanding of technology-based learning media. The positive impact includes changing the mindset of school residents, improving service quality, continuous innovation, and family gathering activities that strengthen the ecosystem relationship between teachers and guardians. This finding confirms that SPMI as an ecosystem that forms a sustainable quality culture contributes significantly to improving the quality of education at SDI Muhammad Hatta and can be a model for other institutions in developing an internal quality assurance system effectively and sustainably.